HTLV-I infection and adult T-cell leukemia in Brazil: an overview - Oliveira, Maria do Socorro Pombo de; Hamerschlak, Nelson; Chiattone, Carlos; Loureiro, Paula (São Paulo Medical Journal, 1996)
Human T-cell lymphotropic Virus Type I (HTLV-I) is the etiologic factor for adult T-cell leukemia/lymphoma (ATL). HTLV-I infection can also lead to other diseases, such as HTLV -I-associated myelopathy/tropical spastic paraparesis (HAM/TSP), uveitis, arthropathy and infectious dermatitis. Studies of the infectious mode of transmission of HTLV-I and risk factors for HTLV-I-related diseases have been conducted in several countries, and differences in the prevalence, age patterns, ethnic groups and clinical presentation of the related diseases have been described worldwide. Based on the geographical characteristics of Brazil and data from the literature, we have summarized the distribution of seroprevalence in blood donors in different states around the country, as well as the incidence of ATL in regards to the endemic foci. ATL in Brazil has the same characteristics as those described elsewhere, but is reported more frequently at a younger age. In order to better evaluate ATL in Brazil, a registry has been established at the several hematologic centers under the sponsorship of the Instituto Nacional de Cancer and the Brazilian Society of Hematology and Hemotherapy, for the purpose of recording all cases originally diagnosed in Brazil.